Economics : a contemporary introduction - McEachern, William A. (Cincinnati, OH : South-Western College, 2000)
Introduction to economics. Fundamentals of macroeconomics. Fiscal and monetary policy. Introduction to the market system. Market structure and pricing. Resource markets. Market failure and public policy. The international setting.
Keywords: Economics; Economics